Pengaruh Tegangan Terhadap Besar Kuat Arus Listrik Pada Pengukuran Hukum OHM Berbasis Simulasi Phet HTML5 - Dewi Tiyas Saputri; Ayu Widiana Putri; Aisyiyah Marfa Berliana Buanasari (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the effect of voltage on the current in an electrical circuit based on Ohm's Law using a PHET simulation. The objective of this research is to understand the relationship between voltage and current when applied to circuits with fixed resistors. The experiment was conducted using PHET simulation software, where voltage was varied from 1 to 9 volts, and current was measured across two resistors with values of 1kΩ and 500Ω. The results show a linear increase in current with increasing voltage, confirming Ohm's Law, where current is directly proportional to voltage and inversely proportional to resistance. The findings imply that simulations can effectively illustrate fundamental electrical principles, offering a practical learning tool for understanding circuit behavior. The study highlights the potential of virtual labs in providing interactive and engaging experiences for students and suggests further research in real-world settings to verify these findings.